A new variable control chart under generalized multiple dependent state sampling. Issue 9 (1st September 2020) - Aslam, Muhammad; Raza, Muhammad Ali; Jun, Chi-Hyuck
Abstract: In this article, we have introduced a new scheme, generalized multiple dependent state (GMDS) sampling by incorporating an additional parameter in the existing MDS to enhance its efficiency, and then integrated it to construct the variable control chart for monitoring the normal process mean. The proposed chart based on GMDS has two pairs of control limits. The charting strategy utilizes the past samples information in conjunction with the current samples information. The performance comparison of the proposed chart with the existing Shewhart type control charts are made by using out-of-control average run length   for various shifts in the process mean. For practical application, two empirical illustrations are provided which establishes the supremacy of the proposed control chart. Simulation study also showed the dominance of the proposed chart over other existing control charts.